Renal and liver injury following the treatment of COVID-19 by remdesivir - Mohsen Mohammad Rahimi; Elham Jahantabi; Behzad Lotfi; Mehdi Forouzesh; Rohollah Valizadeh; Saman Farshid (Society of Diabetic Nephropathy Prevention, 2021)
Remdesivir initially was intravenously administrated to treat the Ebola disease however right now it has been administered to treat COVID-19 in some countries. However it is necessary to find the exact effect of remdesivir in patients with COVID-19. Remdesivir solution is administered with a cyclodextrin carrier that filters solely by the glomeruli; thereby patients with abnormal renal function cannot eliminate it quickly; therefore, remdesivir can lead to renal failure or liver dysfunction during therapeutic process of COVID-19. Assessment of renal function in patients with COVID-19 who have acute kidney injury (AKI) or end-stage renal disease is fundamental.